Patient and family member perspectives on searching for cancer clinical trials: A qualitative interview study. Issue 2 (February 2017) - Ridgeway, Jennifer L.; Asiedu, Gladys B.; Carroll, Katherine; Tenney, Meaghan; Jatoi, Aminah; Radecki Breitkopf, Carmen
Highlights: Patients may delay trial searches but regret it later in the disease course. Patients may want to learn about trials even if they are not ready to participate. Patients may make assumptions about provider roles in extensive trial searches. Family members may provide support for searches, but they worry about raising hopes. Abstract: Objective: Clinical trials are vital in the context of ovarian cancer and may offer further treatment options during disease recurrence, yet enrollment remains low. Understanding patient and family member experiences with identifying trials can inform engagement and education efforts. Methods: Interviews were conducted with 33 patients who had experience with clinical trial conversations and 39 nominated family members. Thematic analysis examined experiences and generated findings for clinical practice. Results: Trial conversations with providers at diagnosis were uncommon and often overwhelming. Most participants delayed engagement until later in the disease course. With hindsight, though, some wished they considered trials earlier. Difficulty identifying appropriate trials led some to defer searching to providers, but then they worried about missed opportunities. Most family members felt unqualified to search. Conclusion: Trial conversations during clinical encounters should start early and include specifying search responsibilities of providers, patients, and family. Patients and family members can be engaged in searches but need guidance. Practice implications: Trials should be discussed throughout the disease course, even if patients are not ready to participate or are not making a treatment decision. Education should focus on identifying trials that meet search criteria. Transparency regarding each individual's role in identifying trials is critical.